Sex Reversal Syndrome in an Egyptian Arabian Horse Detected Using Genomic Data – A case report - Nogueira, Pedro Paulo Oliveira [UNESP]; Amorim, Gabrielle Bueno de Almeida Gonçalves [UNESP]; Oliveira, Odilon Marquez de [UNESP]; Demyda-Peyrás, Sebastián; Santos, Bruna Mendonça [UNESP]; Mota, Lígia Souza Lima Silveira da [UNESP] (Elsevier, 2021)
A 4-year-old Straight Egyptian Arabian horse was evaluated in 2016 due to a malformation of external genitalia and male sexual behavior. On physical examination, small teats in the inguinal area and a rudimentary penis-like structure surrounded by a clitoral fossa could be seen. There was no evidence of vulva and vaginal canal. A stallion like behavior was observed, especially in the presence of mares in heat, when the animal was excited and aggressive and had erection of the penis-like structure. Blood samples were collected for two purposes: hormonal (testosterone and estradiol plasma concentration analyses) and genetic (cytogenetic and molecular analysis). The karyotype showed 32 pairs of chromosomes in all cells (2n = 64) including 14 and 18 pairs of metacentric and acrocentric chromosomes respectively, in agreement with a presumptive 64, XX complement. This result agree with STR and SNP molecular analysis, which also ruled out the possibility of hematopoietic chimerism. In addition, SNP genotyping showed no numerical chromosomal aberrations or large deletions or duplications, that can be linked to the phenotype in any autosome, nor numerical chromosomal abnormalities in the father and mother of the horse analyzed. In conclusion, we determined that the animal in the present study is a male pseudohermaphrodite.
Keywords: Intersexual; Pseudohermaphrodite